Pengembangan Bahan Ajar Berbasis PMRI menggunakan Konteks Olahraga Karate untuk Siswa SD - M, Agnes Verovica; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
Mathematics is considered to be one of the most difficult subjects for most students. The negative effect of this is that many students feel anti-and fearful of learning mathematics before they actually learn mathematics. To increase students' interest in learning mathematics, new innovations are needed, such as the use of the context of karate in learning mathematics. This study aims to improve the learning outcomes of third grade elementary school students by developing teaching materials using the context of karate sports based on Indonesian Realistic Mathematics Education in learning mathematics on arithmetic operations. This research is a development research (Development) which leads to the Plomp development model. Three stages were used in the development of the Plomp model: 1) The initial research stage; 2) The prototype stage; 3) Assessment stage. This study obtained the results of the validity of teaching materials with an average total value of 62 in the very valid category. The results of the practicality level are stated to be practical, this can be seen from the results of teacher responses and student responses. Thus, PMRI-based mathematics teaching materials using the context of karate are declared valid with high and practical categories.